Selling sucks : - Rumbauskas, Frank J. (John Wiley & Sons, Inc., 2007)
Selling Sucks is a must-read for any entrepreneur who wants to run a high-profit, high-integrity business. Rumbauskas's advice is inspiring, clear, and more importantly, easy to implement. It's honestly one of the best how-to self-marketing books on the market. Get this book now if you're serious about exploding your sales and making more money